Sports dentistry principles and practice - Fine, Peter D. 1951- BDS, PhD, DRGP, RCS (Eng); Leung, Albert 1963- BDS, LLM, MA, FDGSRCSI, FFGDP(UK), FHEA; Louca, Chris 1962- BSc, BDS, PhD, AKC (Hoboken, NJ Wiley Blackwell, 2019)
"Sports Dentistry: Principles and Practice is a comprehensive resource that addresses all aspects of this burgeoning field of dentistry. Provides a comprehensive manual that covers the fundamental principles and practice of sports dentistry. Addresses all aspects of sports dentistry, including treatment of injuries, preventative measures, oral health and marketing and practice management. Offers information on providing dental facilities at sporting arenas. Presents suggestions for treating young children and the specific issues they present. Includes a companion website with illustrative case studies"--Provided by publisher.
Sports Dentistry: Principles and practice is a comprehensive resource that addresses all aspects of this burgeoning field of dentistry. The authors - experts in the field - examine effective responses for treating dental trauma and include practical suggestions for preventing acute trauma in the sporting arena. The book discusses dietary implications, nutrition, the need for screening in professional sports, the role oral health plays in sporting performance, saliva, restorative techniques for the traumatised or eroded dentition, and more. This manual's coverage encompasses paediatric dentistry and the specific issues young athletic children encounter, and a useful section of first aid readiness presents procedures that can help ensure adequate care prior to the patient being seen by a sport dentist. This important text: provides a comprehensive manual that covers the fundamental principles and practice of sports dentistry; addresses all aspects of sports dentistry, including treatment of injuries, preventative measures, oral health and marketing and practice management ; Offers information on providing dental facilities at sorting arenas; presents suggestions for treating young children and the specific issues they present. Written primarily for general dental practitioners and specialists in oral and maxillofacial surgery, paediatric dentistry, othodontics, the book is also useful for sports medicine doctors and specialists and physiotherapists. Sports Dentistry offers professionals a thourough review of the most effective dental, endodontic and restorative treatments for sports dentistry
Includes bibliographical references and index
Keywords: Sports Injuries; Sports physical therapy; Athletes; Dentistry -- Practice; Oral medicine